1998
DOI: 10.1046/j.1365-2141.1998.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical study of prognostic factors in childhood acute lymphoblastic leukaemia: differences in outcome are poorly explained by the most significant prognostic variables

Abstract: Summary.We determined the proportion of survival variability explained by the usual prognostic factors in childhood acute lymphoblastic leukaemia (ALL) during a prognostic study of 1552 patients enrolled in three consecutive Fralle group protocols (Fralle 83, Fralle 87 and Fralle 89). The event-free survival rates at 5 years were 54·8% (SD 1·9), 43·1% (SD 2·7) and 55·6% (SD 2·2), respectively. In the univariate analysis the following variables were predictive of poor outcome: male gender, elevated leucocytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 61 publications
(114 reference statements)
0
44
0
Order By: Relevance
“…20,31 The Dutch and Swedish Childhood Leukemia Groups found the diagnostic karyotype to be only of borderline significance as a predictor of outcome. 31,32 Donadieu et al, 3 presented data from 1552 pediatric ALL patients registered in the FRALLE protocols. Using univariate and multivariate analyses, they concluded that the predictive power of chromosome analysis was only 1.6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,31 The Dutch and Swedish Childhood Leukemia Groups found the diagnostic karyotype to be only of borderline significance as a predictor of outcome. 31,32 Donadieu et al, 3 presented data from 1552 pediatric ALL patients registered in the FRALLE protocols. Using univariate and multivariate analyses, they concluded that the predictive power of chromosome analysis was only 1.6.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although many other clinical and biological factors have been identified and assessed for prognostic value, 3 few remain significant when subjected to multivariate analysis. 4,5 One factor that consistently appeared favorable, even in the context of other risk factors, was chromosome number and further analyses suggested the presence of specific chromosomes could be more important than a simple increase in ploidy.…”
Section: Introductionmentioning
confidence: 99%
“…53 In addition to infants, children 410 years also showed a more immature Ig/TCR gene rearrangement pattern, comparable to that seen in adult ALL patients. 30 Interestingly, patients with precursor-B-ALL aged o1 y or 49 years, have a less favorable prognosis, 55,56 comparable to the prognosis of adult patients. So, childhood ALL in patients 410 years is more comparable to adult ALL than to childhood ALL in patients between 1 and 9 years, not only with respect to prognosis but also with respect to the Ig/TCR gene rearrangement pattern.…”
Section: Ig/tcr Genes: Clonality Status and Corearrangementsmentioning
confidence: 99%
“…Patients were treated in accordance with current protocol at the time of leukemia diagnosis, depending on AL type (AML or ALL; that is, FRench group for childhood ALL (FRALLE), European Organisation for Research and Treatment of Cancer (EORTC), Leucémie Aiguë Myéloblastique Enfant (LAME) or ELAM). [19][20][21][22][23] Overall, 16 patients underwent central nervous system irradiation.…”
Section: Patient Characteristicsmentioning
confidence: 99%